2010
DOI: 10.1016/j.jcrysgro.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

In-situ observations of dissolution process of GaSb into InSb melt by X-ray penetration method

Abstract: a b s t r a c tDissolution process of GaSb into InSb melt was observed by an X-ray penetration method. The intensity of X-rays penetrated through the rectangular shaped GaSb (seed)/InSb/GaSb (feed) sandwich sample was recorded by the CdTe line sensor detector. The penetrated X-ray intensities and images of the sample were obtained as a function of time and temperature. The gallium (Ga) composition profile of the sample was calculated as a function of time by making the calibration line with the penetrated X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Solutal Grashof number (GrC) Under normal gravity, the dissolution length at the seed was quite large compared with that at the feed as seen in the in-situ observation 7) by the X-ray penetration method and also in the computed values. Under microgravity, however, the dissolution lengths at the seed and the feed were very close to each other (dashed lines in the middle) due to the suppression of natural convection as expected; dissolution at the seed was reduced while that in the feed was enhanced.…”
Section: Dimensionless Number Definition Valuementioning
confidence: 99%
See 3 more Smart Citations
“…Solutal Grashof number (GrC) Under normal gravity, the dissolution length at the seed was quite large compared with that at the feed as seen in the in-situ observation 7) by the X-ray penetration method and also in the computed values. Under microgravity, however, the dissolution lengths at the seed and the feed were very close to each other (dashed lines in the middle) due to the suppression of natural convection as expected; dissolution at the seed was reduced while that in the feed was enhanced.…”
Section: Dimensionless Number Definition Valuementioning
confidence: 99%
“…The boundary condition used for temperature in this model is slightly different from that of the previous experiment 7) since the temperature on the outer edge of the ampoule could not have been controlled in the experiment. The related physical properties of In x Ga 1-x Sb, GaSb, BN and quartz 9,10) are given in Tables 1, 2, 3 and 4, respectively.…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is mainly due to the suppression of convective flow in the solution (melt). Therefore, several experimental and numerical studies were performed for a better understanding of the InGaSb crystal dissolution and growth process by comparing the terrestrial and microgravity conditions [3][4][5][6][7][8][9]. Also recently Inatomi et al have compared the InGaSb crystals grown on the ISS and on Earth, and demonstrated that the shape of the growth interface was a slightly concave towards the seed under microgravity [10].…”
Section: Introductionmentioning
confidence: 99%